Effects of delayed cord clamping on the third stage of labour, maternal haematological parameters and acid–base status in fetuses at term. (December 2016) - De Paco, Catalina; Herrera, Javier; Garcia, Carolina; Corbalán, Shiana; Arteaga, Alicia; Pertegal, Miriam; Checa, Rosario; Prieto, María Teresa; Nieto, Aníbal; Delgado, Juan Luis
Abstract: Objective: To compare the time in the third stage of labour, differences in maternal hematologic parameters 48 h after birth and acid–base status in the umbilical cord between the early cord clamping (ECC) and delayed cord clamping (DCC). Study design: 97 healthy pregnancies at term and a spontaneous vertex delivery at Clinic University Hospital "Virgen de la Arrixaca" (Murcia, Spain), were randomized to ECC group (<10 s post-delivery) or to DCC group (2 min post-delivery). Duration of the third stage of labour was measured. Samples for acid–base status were taken both from the umbilical artery and vein. Blood samples were taken from the mothers 48 h after birth. Results: No statistical differences were found in the time of the third stage of labour (p = 0.35). No statiscally significant differences were found between the number of red cells (p = 0.25), hemoglobin (p = 0.08) or hematocrit (p = 0.15) in mothers. Umbilical acid–base status or gas analysis did not show any differences between the two groups Conclusions: Delayed cord clamping does not affect significantly the time of the third stage of labour. It does not show either any effect on the hematological parameters in the mother 48 h after birth.